Der mittelalterliche jüdische Friedhof in Erfurt - Karin Sczech (Fasciculi Archaeologiae Historicae, 2023)
In Erfurt, a part of the medieval Jewish cemetery was excavated in 2013. For the first time in Germany, it was possible to carry out both anthropological and genetic studies on the burials recovered there. 14C analyses completed the research. The results are therefore of great importance beyond the site itself. They are a first step towards tracing the migrations of the Jews from late antiquity to the late Middle Ages and researching today’s genetic diseases of Ashkenazi Jews from their origins.